Inflammatory response induced by Helicobacter pylori infection in lung - Arismendi Sosa, Andrea Celeste (2020)
Helicobacter pylori is a microorganism that in the last years has been associated with extragastric disorders such as respiratory diseases, however, its impact on lung is partially understood. The aim of this work was to study infection impact of H. pylori on the inflammatory markers expression at the pulmonary level using an animal model. Infection was performed by BALB/c wild type (WT) mice orotracheal instillation with 20 μl of 1 × 108 H. pylori reference strain suspension once per day throughout 3 days. Inflammatory response was evaluated at 3, 7, 14, 21 and 30 days post infection. Lung was aseptically removed and pulmonary edema index values showed a significant change at 30 days of infection. Hematoxylin-Eosin (H-E) stain allowed to visualizing H. pylori presence in lung samples at 3 days of infection near the phagocytic cells or in the alveoli lumen. Bronchoalveolar lavage (BAL) was used for inflammatory response evaluation. Lactate dehydrogenase values showed a gradual increase in infected animals along infection time. Protein concentrations in mg/ml from BAL increased significantly at 7 days in infected animals. Macrophages viability obtained from BAL, decreased at the first moment of infection, maintaining constant values along contamination time. Results obtained demonstrate an inflammatory response in lung after orotracheal H. pylori infection and suggest that the pathogenic mechanism is strongly evidenced by tissue damage, endothelial dysfunction inflammatory mediators and markers expression at the pulmonary level.